HUBUNGAN TINGKAT PENGETAHUAN DENGAN KETERAMPILAN MAHASISWA D3 KEPERAWATAN SEMESTER 4 DALAM MELAKUKAN TINDAKAN RJP - Marlisa; Dame Evalina Simangunsong; Yohanna Pehulisa Br Surbakti (Poltekkes Kemenkes Medan, 2023)
Cardiopulmonary resuscitation (CPR) is an act of providing compression and ventilation to treat cases of cardiac arrest. Nursing students who will become health workers in the future should have good knowledge and skills to perform CPR. The aim of this study was to find out whether there is a correlation between the level of knowledge and skills of the 4th semester students of the Associate Program in Nursing at Poltekkes Medan, in performing CPR. This research is a correlational quantitative study designed with a cross design, and examines 54 samples obtained through simple random sampling technique. Data regarding knowledge were collected through questionnaires, while data on CPR performed by students were collected through observation. From the results of the study it was found that most of the respondents had a level of knowledge in the good category, where 30 respondents (55.5%) were in the category skilled enough to carry out CPR. Through statistical tests, using Spearman's Rho with SPSS 26, it yields r=0.689 and p-value (0.000)<?(0.05), so it can be concluded that there is a correlation between the level of knowledge and skills in performing CPR. Based on the results of this study, it can be concluded that the level of knowledge and skills possessed by the 4th semester students are mostly in the sufficient category. Students are expected to improve their knowledge and skills in performing CPR by seeking information so they are able to practice their knowledge to patients and the community in need.